Gender-Based Differences in Students’ Critical Thinking on Math Sequences - Muthiah Fildzah Noverli; Nery, Rieno Septra; Hadi, Muhamad Sofian (Plusminus: Jurnal Pendidikan Matematika, 2025)
Berpikir kritis merupakan kompetensi penting dalam pembelajaran matematika abad ke-21, membantu peserta didik menganalisis, mengevaluasi, dan memecahkan masalah secara logis. Penelitian ini membandingkan kemampuan berpikir kritis peserta didik laki-laki dan perempuan pada materi barisan dan deret aritmetika di MTs Jamiatul Qurro Palembang. Desain penelitian yang digunakan adalah deskriptif kualitatif dengan sampel purposif-kelas VIII A dan VIII D dari lima kelas yang ada. Data dikumpulkan melalui dokumentasi, tes uraian berdasarkan indikator berpikir kritis, dan wawancara. Analisis data dilaksanakan dalam tiga tahap: reduksi data, penyajian data, dan penarikan kesimpulan. Hasil menunjukkan bahwa peserta didik perempuan umumnya memiliki kemampuan berpikir kritis lebih tinggi, sedangkan peserta didik laki-laki unggul sekitar 10% pada indikator membuat kesimpulan. Kedua kelompok setara dalam indikator memberikan penjelasan lebih lanjut. Temuan ini menekankan pentingnya strategi pembelajaran yang responsive berbasis gender untuk mengoptimalkan pengembangan berpikir kritis peserta didik. Critical thinking is a key competency in 21st-century mathematics education, supporting students in analyzing, evaluating, and solbing problems logically. Research has shown that gender may influence students’ critical thinking abilities which can impact learning outcomes. This study aimed to compare students’ critical thinking skills based on gender in the context of arithmetic sequences and series at MTs Jamiatul Qurro Palembang. Using a qualitative descriptive design, the study involved one purposively selected class (VIII A and VIII D) from a population of five classes. Data were collected through documentation, essay tests based on critical thinking indicators, and interviews. The analysis followed three stages: data reduction, data presentation, and conclusion drawing. The findings revealed that female students generally demonstrated stronger critical thinking skills, possibly due to more complex cognitive patterns. However, male students outperformed female students by approximately 10% in the indicator of drawing conclusions, likely due to a greater interest in theoretical concepts. Both groups showed similar abilities in providing further explanations. These results highlight the importance of gender-responsive teaching strategies to support the development of students’ critical thinking skills more effectively.